The Role of Mitochondria in Pyroptosis - Li, Qian; Shi, Nengxian; Cai, Chen; Zhang, Mingming; He, Jing; Tan, Ying; Fu, Weijun (Frontiers in Cell and Developmental Biology, 2021)
Pyroptosis is a recently discovered aspartic aspart-specific cysteine protease (Caspase-1/4/5/11) dependent mode of programmed cell death, which is characterized by the rupture of cell membrane perforations and the release of inflammatory cytokines interleukin-1β (IL-1β) and IL-18. Mitochondria also play an important role in apoptotic cell death. When it comes to mitochondrial apoptosis, mitochondrial outer membrane permeabilization (MOMP) is commonly known to commit a cell to die. As a downstream molecule of apoptotic signalling, MOMP participates in the release of cytochrome c from mitochondria and subsequently activate caspase proteases. Hence, targeting MOMP for the sake of manipulating cell death presents tremendous therapeutic potential among various diseases, such as autoimmune disorders, neurodegenerative diseases and cancer. In this review, we highlights the roles and significance of mitochondria in pyroptosis to provide unexplored strategies that target the mitochondria to regulate cell death for clinical benefit.